Melatonin in Hypoxic-Ischemic Brain Injury in Term and Preterm Babies - Justyna Paprocka; Marek Kijonka; Beata Rzepka; Maria Sokół (International Journal of Endocrinology)
Melatonin may serve as a potential therapeutic free radical scavenger and broad-spectrum antioxidant. It shows neuroprotective properties against hypoxic-ischemic brain injury in animal models. The authors review the studies focusing on the neuroprotective potential of melatonin and its possibility of treatment after perinatal asphyxia. Melatonin efficacy, low toxicity, and ability to readily cross through the blood-brain barrier make it a promising molecule. A very interesting thing is the difference between the half-life of melatonin in preterm neonates (15 hours) and adults (45-60 minutes). Probably, the use of synergic strategies—hypothermia coupled with melatonin treatment—may be promising in improving antioxidant action. The authors discuss and try to summarize the evidence surrounding the use of melatonin in hypoxic-ischemic events in term and preterm babies.